Penerapan Aplikasi E-Perkara di Pengadilan Agama Jakarta Barat dengan Model Agile Development - Galuh Saputri; Agung Siswopranoto (Faktor Exacta, 2025)
The West Jakarta Religious Court is part of the Supreme Court of the Republic of Indonesia, which currently still uses conventional methods to recapitulate the percentage of case types. Based on the results of observations, the Chairman of the West Jakarta Religious Court must review the recapitulation of the percentage of cases from the clerk's department. After receiving the recapitulation, the leadership needs to review the report and ask for further information from the Registrar of the West Jakarta Religious Court. The process of processing case data which is still conventional causes slow recapitulation of case settlement percentages and requires a lot of paper for each case, which then requires large archive storage space, and there is a risk of the archives being slipped or lost. To overcome this problem, the proposed solution is to build a Website-based E-Case application for the West Jakarta Religious Court, using an Agile Development approach. With this E-Case application, the overall case data recapitulation process can be carried out online/electronically to make it easier to delegate tasks. This is proven by the results of a questionnaire using the System Usability Scale test, which showed results of 79.50% from Employees and 81.25% from Admin.